Shortcomings of the Brazilian Pre-Salt Auction Design - Araujo,Aloisio (2016)
The Brazilian government instituted a new regulatory framework for auctioning pre-salt oil reserves to replace the previous concession regime with a profitshare bidding auction. Motivated by the new rules, we present a model of revenue share bidding auction under affiliation. We prove the existence of monotone pure-strategy equilibrium and characterize its equilibrium bidding function. In addition, we prove that it generates an expected revenue at least as large as the usual bonus bidding auction. Next, we introduce in the model a function representing a royalty rate that is contingent on the value of the object. We suggest instrument improves expected revenue in both models, reducing the gap between them. Analyzing this new regulatory framework from the viewpoint of theoretical and numerical results obtained, we discuss some consequences and argue that the previous regime dominates the new one.